2021
DOI: 10.1097/gox.0000000000003823
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patient Expectations before Carpal Tunnel Release

Abstract: Background: Carpal tunnel release (CTR) is common, yet patient treatment expectations remain unclear. The primary purpose was to describe patient expectations before CTR. Secondarily, we aimed to identify factors influencing expectations. Methods: Included patients underwent unilateral or bilateral CTR between 2015 and 2017 at a single academic center. Expectations regarding the level of relief/improvement were queried. Area deprivation index (ADI) was used to measure social deprivation. Univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Rogers et al found that male gender, lower BMI, and lower social deprivation correlated with significantly increased expectations before carpal tunnel release. 34 While our univariable analysis did identify employment, revision CuTR, lower levels of social deprivation, and type of insurance (Medicare, Medicaid) as associated with expecting great relief/improvement, the multivariable analysis highlighted a significant increase in expectations before CuTR, specifically in patients with Medicare and Medicaid. This is concerning given that surgical outcomes have been found to be significantly worse in the Medicaid and Medicare populations.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Rogers et al found that male gender, lower BMI, and lower social deprivation correlated with significantly increased expectations before carpal tunnel release. 34 While our univariable analysis did identify employment, revision CuTR, lower levels of social deprivation, and type of insurance (Medicare, Medicaid) as associated with expecting great relief/improvement, the multivariable analysis highlighted a significant increase in expectations before CuTR, specifically in patients with Medicare and Medicaid. This is concerning given that surgical outcomes have been found to be significantly worse in the Medicaid and Medicare populations.…”
Section: Discussionmentioning
confidence: 71%
“…22 Additionally, specific to hand surgery, lower social deprivation has been associated with greater expectations for improvement after carpal tunnel release. 34 The ADI evaluates 17 factors that influence socioeconomic status, including education level, income, and housing type for a given 9 digit zip code, 35 which is granular to the level of 10-20 homes on average. 36 These data were originally collected from census records based on the Health Resources and Services Administration, and are updated regularly to include the most recent American Community Survey data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation